2020
DOI: 10.3390/geriatrics5040063
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Mediation of the Effects of Physical Activity on Cognitive Function by the Gut Microbiome

Abstract: The population of older adults is growing dramatically worldwide. As older adults are at greater risk of developing disorders associated with cognitive dysfunction (i.e., dementia), healthcare costs are expected to double by 2040. Evidence suggests dementia may be slowed or prevented by lifestyle interventions, including physical activity (PA). PA is associated with improved cognitive function and may reduce risk for dementia by mitigating known risk factors (i.e., cardiovascular diseases) and/or by enhancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 275 publications
(325 reference statements)
0
6
0
Order By: Relevance
“…PA/exercise might be a way to improve the gut microbiome during ageing since it influences several organs, cells, and tissues, and involves several molecular pathways. Previous studies have shown that PA/exercise have several benefits during the ageing process such as improvements in cognitive function [ 55 , 56 ], promotion of cardiovascular health [ 57 ] and improvements in the musculoskeletal system [ 58 , 59 , 60 ], making it a precious tool to counteract the age-associated changes that occur in those systems. Besides the benefits mentioned previously, recent studies [ 61 , 62 , 63 , 64 ] on the effects of exercise on the gut microbiome of older people have suggested that exercise might beneficially affect its composition and even reverse some age-associated taxonomical changes, ultimately leading towards healthy ageing.…”
Section: Introductionmentioning
confidence: 99%
“…PA/exercise might be a way to improve the gut microbiome during ageing since it influences several organs, cells, and tissues, and involves several molecular pathways. Previous studies have shown that PA/exercise have several benefits during the ageing process such as improvements in cognitive function [ 55 , 56 ], promotion of cardiovascular health [ 57 ] and improvements in the musculoskeletal system [ 58 , 59 , 60 ], making it a precious tool to counteract the age-associated changes that occur in those systems. Besides the benefits mentioned previously, recent studies [ 61 , 62 , 63 , 64 ] on the effects of exercise on the gut microbiome of older people have suggested that exercise might beneficially affect its composition and even reverse some age-associated taxonomical changes, ultimately leading towards healthy ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Physical exercise is classified according to the type and intensity into dynamic and static, and based on muscle metabolism, into aerobic and anaerobic [36,37]. Most static exercises, such as muscle building, weightlifting, Tai Chi, and Yoga and Benson relaxation, are performed anaerobically, while dynamic exercises lasting for more than several minutes require increased heart and breathing rates to maintain exercise sessions, and could be low-tomoderate, such as walking, jogging, and cycling, and vigorous exercise, like football, treadmill running and swimming [37][38][39].…”
Section: General Classes Of Physical Exercisementioning
confidence: 99%
“…Furthermore, metabolic equivalent units (METs) are often used to classify aerobic physical exercise as light-to-mild, moderate, or vigorous, where METs refer to the amount of oxygen consumed during exercise compared to the rest status, and 1 MET typically equals 3.5 ml O 2 /kg body weight/ minute [36]. Accordingly, the low-to-mild, moderate, and vigorous exercises equal (1.6-2.9 METs), (3-6 METs), and (> 6 METs), respectively [38].…”
Section: General Classes Of Physical Exercisementioning
confidence: 99%
See 2 more Smart Citations